DIGESTIBILITY OF NUTRIENTS IN THE DIET DURING THE EARLY GROWTH PERIOD OF GOATS - Fayzullayev , Ikrom Alisherovich; Nakhalboyev , Alisher Aliboyevich (Innovative Development in Educational Activities, 2023)
In the article goats digestion of nutrients in the diet during the initial stage of constipation about info given.